Potential Nosocomial Acquisition of Epidemic Listeria monocytogenes Presenting as Multiple Brain Abscesses Resembling Nocardiosis - Aleksandra Stefanovic; James Reid; A Celine Nadon; Jennifer Grant (Canadian Journal of Infectious Diseases and Medical Microbiology)
Listerial brain abscesses are rare, and are found mostly in patients with underlying hematological malignancies or solid-organ transplants. A case of a patient with Crohn’s disease and multiple brain abscesses involving the left cerebellum and right sylvian fissure is described. The Gram stain and histopathology of the cerebellar abscess revealed Gram-positive, beaded rods suggestive of Nocardia. However, on culture, Listeria monocytogenes was identified. Listeria may appear Gram-variable and has been misidentified as streptococci, enterococci and diphtheroids. The present case is the first reported case of L monocytogenes resembling Nocardia on both microbiological and histopathological assessment. Reported cases of listerial brain abscesses are sporadic, while the current case was part of a nationwide listerial outbreak linked to consumption of contaminated deli meats. Broad antimicrobial therapy (including antilisterial coverage) in immunosuppressed patients presenting with brain abscess is crucial, until cultures confirm the identification of the organism.